2018
DOI: 10.1093/ptj/pzy135
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Clinical Education Strategic Initiatives Project—Development of Parameters to Guide Harmonization in Clinical Education: A Scoping Review

Abstract: Background Clinical education curricular models specifically related to integrated clinical education (ICE) vary across physical therapist education programs. The interconnectedness of ICE to the advancement of a shared vision for clinical education in professional physical therapist education needs investigating. Purpose The purpose of this scoping review was to: (1) define ICE, (2) define baseline expectations and parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These opportunities are designed by faculty to meet specific learning objectives while preparing students for full-time clinical education by promoting the 4 'Cs': confidence, communication skills, clinical reasoning, and clinical skill development. 2 Various models of ICE exist in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15] They vary by sequencing and placement within the curriculum, frequency, format, setting, and by who supervises the students.…”
Section: T He American Council Of Academic Physicalmentioning
confidence: 99%
See 1 more Smart Citation
“…These opportunities are designed by faculty to meet specific learning objectives while preparing students for full-time clinical education by promoting the 4 'Cs': confidence, communication skills, clinical reasoning, and clinical skill development. 2 Various models of ICE exist in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15] They vary by sequencing and placement within the curriculum, frequency, format, setting, and by who supervises the students.…”
Section: T He American Council Of Academic Physicalmentioning
confidence: 99%
“…A scoping review of the literature found that 10 of the 11 articles addressing ICE in physical therapy education presented with low methodological quality, 2 which stemmed from a lack of systematic collection and analysis of program assessment data, and bias within selected program assessment tools. 2 The ICE experiences described were based upon practice settings (outpatient, 4,7,9 ICU, 4,9 acute, 4,7,9 inpatient rehabilitation, 4 subacute, 4,9 long term, 7 schools, 7 wellness, 12 or onsite clinic 12 ) or specific diagnoses and were not exclusive to older adults.…”
Section: T He American Council Of Academic Physicalmentioning
confidence: 99%
“…11 Panels were created to address CE common terminology, integrated CE, and student readiness prior to a first full-time CE experience. 1,12,13 e work established by the CE Summit broadly represented professional PT education but did not speak to the specific CE needs of different practice settings nor address the lack of CE teaching resources. 11 e Academy of Pediatric Physical erapy (APPT) convened Education Summit I in 2012 to address the documented inconsistencies and variability in pediatric physical therapy education.…”
Section: Introduction/ Literature Reviewmentioning
confidence: 99%
“…11 Panels were created to address CE common terminology, integrated CE, and student readiness prior to a first full-time CE experience. 1,12,13 The work established by the CE Summit broadly represented professional PT education but did not speak to the specific CE needs of different practice settings nor address the lack of CE teaching resources. 11…”
Section: Introduction/literature Reviewmentioning
confidence: 99%
“…In addition to the didactic training, physical therapy students take part in several different clinical rotations during their academic training. It is, however, widely agreed that additional course-embedded clinical experiences are also necessary to help link didactic knowledge with clinical skills [6][7][8][9]. With the aging population and need for geriatric professionals growing, there has been an increase in the number of students enrolled in most health professions programs across the country.…”
Section: Introductionmentioning
confidence: 99%